Temporal changes in soil C‐N‐P stoichiometry over the past 60 years across subtropical China. (30th October 2017) - Yu, Zaipeng; Wang, Minhuang; Huang, Zhiqun; Lin, Teng‐Chiu; Vadeboncoeur, Matthew A.; Searle, Eric B.; Chen, Han Y. H.
Abstract: Controlled experiments have shown that global changes decouple the biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P), resulting in shifting stoichiometry that lies at the core of ecosystem functioning. However, the response of soil stoichiometry to global changes in natural ecosystems with different soil depths, vegetation types, and climate gradients remains poorly understood. Based on 2, 736 observations along soil profiles of 0–150 cm depth from 1955 to 2016, we evaluated the temporal changes in soil C‐N‐P stoichiometry across subtropical China, where soils are P‐impoverished, with diverse vegetation, soil, and parent material types and a wide range of climate gradients. We found a significant overall increase in soil total C concentration and a decrease in soil total P concentration, resulting in increasing soil C:P and N:P ratios during the past 60 years across all soil depths. Although average soil N concentration did not change, soil C:N increased in topsoil while decreasing in deeper soil. The temporal trends in soil C‐N‐P stoichiometry differed among vegetation, soil, parent material types, and spatial climate variations, with significantly increased C:P and N:P ratios for evergreen broadleaf forest and highly weathered Ultisols, and more pronounced temporal changes in soil C:N, N:P, and C:P ratios at low elevations. Our sensitivity analysis suggests that the temporal changes in soil stoichiometry resulted from elevated N deposition, rising atmospheric CO2 concentration and regional warming. Our findings revealed that the responses of soil C‐N‐P and stoichiometry to long‐term global changes have occurred across the whole soil depth in subtropical China and the magnitudes of the changes in soil stoichiometry are dependent on vegetation types, soil types, and spatial climate variations. Abstract : During the study period, atmospheric CO2 concentration and annual temperature anomalies significantly increased, while precipitation anomalies slightly decreased across subtropical China. The responses of soil C‐N‐P and stoichiometry to rising atmospheric CO2 concentration and temperature anomalies were similar, with significantly decreased soil total P concentrations and increased ratios of C:N, C:P, and N:P.